Effects of DOACs on Mouse Melanoma Metastasis and the Inhibitory Mechanism of Edoxaban, a Factor Xa-Specific DOAC - Hiramoto, Keiichi; Watanabe, Taisei; Imai, Masashi; Suzuki, Koji (TH Open, 2025)
Direct oral anticoagulants (DOACs) have been widely used in patients with thromboembolism. We previously reported that among DOACs, edoxaban (EDX), a factor Xa (FXa)-specific DOAC, most effectively inhibited the growth of syngeneic non-metastatic murine colon cancer cells implanted in mice via the protease-activated receptor 2 (PAR2) pathway. This study aimed to analyze the effects and mechanism of action of DOACs targeting thrombin or FXa on the metastasis of murine melanoma B16 cells implanted in mice.B16 cells (106 cells in 100 μL) were implanted into the tail vein of 8-week-old female C57BL/6j mice (n = 5 per group), followed by daily oral administration of DOACs targeting thrombin (dabigatran etexilate [DABE], 50 mg/kg body weight [bw]) or FXa (rivaroxaban [RVX], 5 mg/kg bw; EDX, 10 mg/kg bw) for 14 days. The effects on tumor metastasis on day 15 and the inhibitory mechanism of the DOAC with the strongest inhibitory effect were analyzed.Lung metastasis of B16 cells implanted in mice was significantly suppressed in the following order: EDX > RVX ≥ DABE, compared with the saline-treated group. DOPA (3,4-dihydroxyphenylalanine)-positive cell density was significantly reduced from approximately 1,250 cells/mm2 in the saline group to approximately 600 cells/mm2 (RVX and DABE) and approximately 400 cells/mm2 (EDX; p < 0.05 or 0.01). Investigating the inhibitory mechanism of EDX revealed that inflammation-associated factors such as PAR2, interleukin 6 (IL-6), and transforming growth factor β1 (TGFβ1); angiogenic factors such as vascular endothelial growth factor A and angiopoietin-2; and epithelial–mesenchymal transition (EMT)-associated factors such as vimentin and snail, which were increased in the lungs of the saline-treated group, all significantly decreased in the EDX-treated group (p < 0.05 or 0.01). In contrast, intercellular tight junction factors exhibited an opposite trend. EDX also inhibited FXa-dependent production of melanin, IL-6, and TGFβ1 in in vitro cultured B16 cells.Among the tested DOACs, EDX showed the strongest inhibition of B16 cell metastasis in mice, likely via the suppression of inflammation, angiogenesis, and EMT mediated by the FXa-dependent PAR2 and TGFβ pathways in tumor and surrounding tissue cells.
Keywords: DOAC; edoxaban; PAR2; IL-6; TGFβ1; B16 melanoma cells; tumor metastasis; C57BL/6j mice